Profile of Acute Pharyngitis at Dr. Soetomo General Hospital Pediatric Outpatients Clinic in 2013 - Amanda Trilana; Dwi Susanti; Satrio Boediman (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Acute Pharyngitis remains a common health problem in the world, especially in developing countries andmostly infects children. Around 6,2 to 9,7 million children worldwide went to clinics and emergency department with pharyngitis. This study aims to find the characteristic of acute pharyngitis in childen at Dr. Soetomo Hospital Surabaya.Methods: This study was a cross sectional, using medical records of acute pharyngitis patients in pediatric outpatient clinic. Data collected based on age, sex, chief complaint, additional complaints and clinical signs.Results: Total samples were 92 patients with sex proportion of 48 males (52,2%) and 44 females (47,8%). Based on age, mostly at 0 – 3 years old (68,4%). The most common chief complains were fever, followed by cough and sore throat for 55,4%, 28,2% and 16,4% respectively. Based on additional complain, 56,5% still has good appetite. Based on clinical signs, hyperemic pharyngeal was 91,3% and lymph nodes enlargement was 8,7%.Conclusion: Acute pharyngitis mostly infected toddler characterized with fever, and hyperemic pharyngeal as a clinical sign.